New reflector shaping methods for dual-reflector antenna - Quzwain, Kamelia; Yamada, Yoshihide; Kamardin, Kamilia; Abd Rahman, Nurul Huda; Ismail, Alyani (Czech Technical University in Prague, 2022)
In the fifth-generation (5G) mobile system, new millimeter-wave technologies such as small cell size and multibeam operation are introduced at the base station. Currently, the hybrid beam forming array antennas are developed for beam steering operations. However, the array antenna configuration has drawback of increased feed circuit loss and antenna gain reduction. Moreover, many modulation/demodulation circuits increase the antenna price. The reflector antenna is another option for multi beam operations that has high gain and small feeder loss. The problem of the reflector antenna is how to achieve good multi beam radiation patterns. Previously, reflector shaping method of the dual reflector antenna was proposed. However, previous method can’t apply for good multi beam designing. In this paper, modification to the reflector shaping method using equivalent parabola reflector and equivalent circle reflector method is proposed to achieve a good multi beam radiation patterns. First, the equivalent parabola and circle equation is implemented in the reflector shaping algorithms. Second, a Matrix Laboratory (MATLAB) program is developed in order to obtain the main and sub reflector shapes. The accuracy of MATLAB program is ensured from the obtained ray path results, aperture distribution and radiation pattern. In the final step, multi beam performance is validated using an electromagnetic simulator, FEKO. Through comparison of the equivalent parabola with the equivalent circle reflectors, an antenna efficiency of 67.6% is obtained and better multi beam radiation patterns are demonstrated using the equivalent circle reflector. Therefore, the usefulness of the newly developed shaping method employing equivalent circle reflector is ensured.